Creating simulation activities for undergraduate nursing curricula - McGough, Shirley; Heslop, K. (2016)
Simulation is considered a valuable educational strategy to prepare nursing students for clinical practice and bridge the gap between theory and clinical experience (Unsworth et al. 2012) with Milkins et al. (2014) advocating for the use of simulation in student education to support the National Safety and Quality Health Service Standards (NSQHSS) (Australian Commission on Safety and Quality in Health Care (ACSQHC), 2012).